Coauthor Network Analysis of Journal of Applied Communications Articles from 2008-2017 - Audrey E. H. King; Quisto Settle (Journal of Applied Communications, 2019)
Coauthorship networks offer a glimpse of collaborations within a discipline, illustrating the social networks that enable users to leverage more resources than they could on their own. This study used relational bibliometric data from the last 10 years of the Journal of Applied Communications (JAC) to create a social network analysis. The following research objectives guided this study: 1) Describe authorship, category (i.e., research article, commentary, book review), and number of JAC papers published from 2008 to 2017, 2) Describe the coauthor network characteristics of JAC papers, and 3) Describe the relationship between publication frequency and social network characteristics of authors. Results showed the majority of articles published in JAC were research articles and written by more than one author. Typically, authors who were well connected in the network were those who collaborated with other faculty at their own institution and continued to collaborate with graduate school classmates after graduation. Based on the results, recommendations to broaden connections in agricultural communications included increasing collaborations based on research interests, as opposed to geographic proximity and past working relationships to increase connections across the agricultural communications discipline.
Keywords: social network analysis; Journal of Applied Communications; authorship; social capital